2012
DOI: 10.1002/ijc.27870
|View full text |Cite
|
Sign up to set email alerts
|

Functional effect of polymorphisms in 15q25 locus on CHRNA5 mRNA, bulky DNA adducts and TP53 mutations

Abstract: Genome-wide association studies have demonstrated that genetic polymorphisms influence the risk of developing lung cancer. Nicotinic acetylcholine receptor alpha3, alpha5 and beta4 genes (CHRNA3, CHRNA5 and CHRNB4) cluster at the 15q25.1 lung cancer susceptibility locus. We genotyped 310 patients with non-small cell lung cancer and a control group of 348 cancer-free individuals for seven sequence variants located in CHRNA3 and CHRNA5 genes. Two of the polymorphisms (rs3829787 and rs3841324) statistically influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…The GWAS SNPs at 15q25.1 were reported to be associated with total expression levels and multiple isoforms of CHRNA5 in normal lung tissue samples 37,38 . The GWAS SNPs at the other four loci have not been reported to be associated with the total expression of nearby genes.…”
Section: Resultsmentioning
confidence: 99%
“…The GWAS SNPs at 15q25.1 were reported to be associated with total expression levels and multiple isoforms of CHRNA5 in normal lung tissue samples 37,38 . The GWAS SNPs at the other four loci have not been reported to be associated with the total expression of nearby genes.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, cigarette smoking, which is one of the main causes of NSCLC and has also been related to prognosis in NSCLC patients treated with cisplatin and gemcitabine or cisplatin and pemetrexed [26], leads to more copy number alterations, which may be mediated by the genome instability [27]. A recent study showed that nicotinic acetylcholine receptor alpha3, alpha5, and beta4 genes (CHRNA3, CHRNA5, and CHRNB4) cluster at the 15q25.1 lung cancer susceptibility locus, and four variants (rs3829787, rs3841324, rs588765, and rs3743073) were associated with differential levels of genetic aberrations, while three haplotypes were associated with CHRNA5 mRNA levels, susceptibility to NSCLC, smoking-related DNA alterations, and TP53 mutations [28]. Genetic differences resulting in interindividual variation in DNA repair capacity may indeed account for susceptibility of the lung cells to the genotoxic agents leading to somatic mutations, and individuals who smoke and have polymorphisms that may result in deficient DNA repair are at a greater risk of TP53 mutations.…”
Section: Pharmacogenetics Of Nsclc: Which Genes Copy Number Variatiomentioning
confidence: 99%
“…Recently, the locus containing two genes encoding nicotine acetylcholine receptor (nAChR) subunits, CHRNA3 and CHRNA5, was shown to be associated with lung cancer risk in Caucasians by three genome-wide association studies [17,19,20]. A decreased survival correlation with lung cancer has been shown because the reduced treatment e cacy and worse survival may be well explained by the nAChRs pathway through CHRNA proteins on tumor cell proliferation, apoptosis, epithelial-mesenchymal transition, and proinvasive and angiogenic effects [21,22]. Our results showed that CHRNA5 was higher expressed in lung adenocarcinoma tissues, and that there is a signi cant association between the expression and clinical characteristics and patient prognosis.…”
Section: Discussionmentioning
confidence: 99%